Rain rate and radon daughters' activity. (1st October 2020) - Bottardi, Carlo; Albéri, Matteo; Baldoncini, Marica; Chiarelli, Enrico; Montuschi, Michele; Raptis, Kassandra Giulia Cristina; Serafini, Andrea; Strati, Virginia; Mantovani, Fabio
Abstract: During a precipitation a transient increase of gamma activity is generated by 214 Pb and 214 Bi, daughters of atmospheric 222 Rn, which are collected by rain droplets and brought to the ground. A continuous monitoring of this gamma radiation can be an efficient alternative to a 222 Rn direct measurement in clouds and allows for estimating rain-induced variations in environmental gamma radiation. This work presents the results of a seven months proximal gamma-ray spectroscopy experiment, specifically tailored for gathering reliable and unbiased estimates of atmospheric 214 Pb gamma activity related to rainfalls. We developed a reproducible model for reconstructing the temporal evolution of the 214 Pb net count rate during rain episodes as function of the rain rate. The effectiveness of the model is proved by an excellent linear correlation (r 2 = 0.91) between measured and estimated 214 Pb count rates. We observed that the sudden increase of 214 Pb count rates ( Δ C ) is clearly related to the rain rate (R) by a power law dependence Δ C ∝ R 0.50 ± 0.03 . We assessed that the radon daughter 214 Pb content (G) of the rain water depends on the rain rate with G ∝ 1 / R 0.48 ± 0.03 and on the rain median volume diameter ( λ m ) with G ∝ 1 / λ m 2.2 . We proved that, for a fixed rainfall amount, lower is the rainfall intensity (i.e. the longer is the rain duration), higher is the radon daughters' content of the rain water. Graphical abstract: Image 1 Highlights: Every impulse of rain produces a sudden increase of 214 Pb gamma activity. A reproducible model reconstructs the temporal evolution of the 214 Pb count rate. For a fixed rainfall amount longer events correspond to higher 214 Pb content. Gamma-ray spectroscopy can discriminate between irrigation and rainfall. Increase of radon daughters' activity depends on the square root of the rain rate.